AN INDEX TO THE BIBLICAL PASSAGES CITED IN FRANZ ROSENTHAL, A GRAMMAR OF BIBLICAL ARAMAIC - Wilson, Gerald Henry (Journal of Semitic studies, 1979)
GERALD H. WILSON; AN INDEX TO THE BIBLICAL PASSAGES CITED IN FRANZ ROSENTHAL, A GRAMMAR OF BIBLICAL ARAMAIC, Journal of Semitic Studies, Volume 24, Issue 1, 1 M